2021
DOI: 10.3390/foods10123113
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Profile of Dry and Wet Aged Beef Loin and Its Relationship with Consumer Flavour Liking

Abstract: This study investigated the effect of ageing method and ageing time on the volatile profiles of grilled beef striploins (Longissimus thoracis et lumborum) and their relationship with consumer flavour liking. Volatiles were measured in grilled steaks subjected to 35 days of dry ageing, 35 days of wet ageing, 56 days of dry ageing or 56 days of wet ageing, using headspace-solid-phase microextraction followed by gas chromatography-mass spectrometry. Gas chromatography-olfactometry-mass spectrometry was also condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The following supporting information can be downloaded at: , Table S1: Definitions and standard references for descriptive beef flavor and texture attributes where 0 = extremely dry/tough/not detectable and 100 = extremely juicy/tender/intense, from Adhikari et al [ 10 ] and AMSA [ 27 ]; Table S2: Retention time, fragment ions, and odor descriptors of volatile compounds identified in three plant-based meat alternatives and two lean levels of ground beef [ 29 , 30 ].…”
mentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Definitions and standard references for descriptive beef flavor and texture attributes where 0 = extremely dry/tough/not detectable and 100 = extremely juicy/tender/intense, from Adhikari et al [ 10 ] and AMSA [ 27 ]; Table S2: Retention time, fragment ions, and odor descriptors of volatile compounds identified in three plant-based meat alternatives and two lean levels of ground beef [ 29 , 30 ].…”
mentioning
confidence: 99%
“…As shown in Figure 2 , after 42 days of traditional dry-ageing, dramatic increasing trends were detected in aldehydes (3-methylbutanal, 2-methylbutanal, benzene acetaldehyde, E-2-heptenal, nonanal, octanal, heptanal, and pentanal), ketones (2-heptanone), alcohols (1-octene-3-ol, pentanol, 2-methylpropanol, and ethanol), furans (2-pentylfuran), and esters (butyl acetate and butyl propanoate). Similarly, Lee et al [ 29 ] and Li et al [ 30 ] reported that dry-ageing increased concentrations of aldehydes, ketones, and alcohols. 3-methylbutanal (malty odor), 2-methylbutanal (chocolate odor), and benzene acetaldehyde (rosy odor) come from the Strecker degradation of leucine, isoleucine, and phenylalanine, respectively [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 88%
“…As mentioned above, aldehydes have intense volatile and fatty aromas and are crucial volatile aroma components of grilled lamb and other meats. For example, the aroma of 3-methyl butanal has been described as brothy, meaty, or malty ( Li, Han, Frank, McGilchrist, & Warner, 2021 ). Additionally, long-chain aldehydes, such as (E)-2-nonenal and (E)-2-decenal, contribute a linseed oil odor.…”
Section: Resultsmentioning
confidence: 99%